1998
DOI: 10.1021/bi981509y
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenase of Azotobacter vinelandii: Kinetic Analysis of the Fe Protein Redox Cycle

Abstract: Nitrogenase consists of two metalloproteins (Fe protein and MoFe protein) which are assumed to associate and dissociate to transfer a single electron to the substrates. This cycle, called the Fe protein cycle, is driven by MgATP hydrolysis and is repeated until the substrates are completely reduced. The rate-limiting step of the cycle, and substrate reduction, is suggested to be the dissociation of the Fe protein-MoFe protein complex which is obligatory for the reduction of the Fe protein [Thorneley, R. N. F.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 38 publications
5
44
0
Order By: Relevance
“…These facts and the observations of alginate formation, its variation in quality, and especially the varied morphology of the alginate capsule on the cell surface strongly suggested that the formation of alginate (capsule) plays an important role in overcoming oxygen stress and regulating the nitrogenase activity and hence the growth of A. vinelandii, particularly under phosphate-limited conditions. This conclusion is also supported by several other previous observations: (i) the production of alginate takes place mainly in the phosphate-limited phase in batch culture (38), (ii) growth in the presence of ammonium (the final product of nitrogen fixation) inhibits alginate formation in A. vinelandii (5,37), and (iii) alginate production is stimulated under conditions of limited synthesis of nitrogenase caused by limitation of either molybdate or iron (1,10 The protective role of alginate has also been demonstrated for Pseudomonas aeruginosa with respect to growth stresses caused by antibiotics, virulent phages, and metal toxicity (13,23). However, for A. vinelandii and P. aeruginosa, the mechanisms by which alginate exerts its protective role are so far not well understood.…”
Section: Discussionsupporting
confidence: 87%
“…These facts and the observations of alginate formation, its variation in quality, and especially the varied morphology of the alginate capsule on the cell surface strongly suggested that the formation of alginate (capsule) plays an important role in overcoming oxygen stress and regulating the nitrogenase activity and hence the growth of A. vinelandii, particularly under phosphate-limited conditions. This conclusion is also supported by several other previous observations: (i) the production of alginate takes place mainly in the phosphate-limited phase in batch culture (38), (ii) growth in the presence of ammonium (the final product of nitrogen fixation) inhibits alginate formation in A. vinelandii (5,37), and (iii) alginate production is stimulated under conditions of limited synthesis of nitrogenase caused by limitation of either molybdate or iron (1,10 The protective role of alginate has also been demonstrated for Pseudomonas aeruginosa with respect to growth stresses caused by antibiotics, virulent phages, and metal toxicity (13,23). However, for A. vinelandii and P. aeruginosa, the mechanisms by which alginate exerts its protective role are so far not well understood.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the extensive changes observed in Kp2 and Av2 in the transition state complexes must primarily arise from the interaction with the MoFe protein; the role of the nucleotide may thus be to prime the interaction region of the Fe protein to respond to the MoFe protein. Consistent with this, Duyvis et al (24) recently proposed from pre-steady state kinetic data that MgATP interacts with the A. vinelandii nitrogenase complex to trigger the conformational changes that are essential for effective electron transfer. We note that the surface incompatibility of Av1 and Av2 necessitates the large scale conformational changes in Av2 to accommodate specific interactions between the two proteins (20).…”
Section: Solution Structure Of 1:1 Complex and Changes In The Fementioning
confidence: 73%
“…23 for discussion) lacks firm experimental evidence and has been questioned recently. An alternative, in which MgATP binds rapidly to a complex of Fe and MoFe proteins, followed by subsequent conformational changes in the Fe protein, has been proposed (24). Moreover, in the heterologous nitrogenase formed between the Fe protein of C. pasteurianum and the MoFe protein from A. vinelandii, MgATP is not required for complex formation (25,26).…”
mentioning
confidence: 99%
“…During catalytic turnover, the [Fe 4 S 4 ] cluster cycles between the oxidized 2+ and reduced +1 states. The +1 state is accessed in vitro with the reductant dithionite, whereas the in vivo reduction of NifH can be driven by physiological reductants such as flavodoxin and ferredoxin [26][27][28][29][30]. Mechanistic studies of electron transfer from NifH to NifDK suggest that upon complexation, the first electron transfer event occurs from the P-cluster to the active site M-cluster, after which the [Fe 4 S 4 ] cluster of NifH reduces the now-oxidized P-cluster [31].…”
Section: Electron Transfer For Nitrogenase Catalysismentioning
confidence: 99%